2021
DOI: 10.1186/s12940-021-00714-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic exposure to air pollution in relation with incidence, prevalence, severity and mortality of COVID-19: a rapid systematic review

Abstract: Background Air pollution is one of the world’s leading mortality risk factors contributing to seven million deaths annually. COVID-19 pandemic has claimed about one million deaths in less than a year. However, it is unclear whether exposure to acute and chronic air pollution influences the COVID-19 epidemiologic curve. Methods We searched for relevant studies listed in six electronic databases between December 2019 and September 2020. We applied no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 82 publications
0
41
0
1
Order By: Relevance
“…Since the beginning of the COVID-19 pandemic, there have been several studies published on the associations between long-term air pollution and COVID-19 mortality; however, many of these studies did not control for potential confounding factors, such as population size or demographics ( Katoto et al, 2021 ; Ali and Islam, 2020 ; Copat et al, 2020 ; Domingo et al, 2020 ). Among studies with some consideration of potentially confounding variables, several have reported positive associations between COVID-19 mortality and long-term air pollution concentrations, primarily PM 2.5 and NO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the beginning of the COVID-19 pandemic, there have been several studies published on the associations between long-term air pollution and COVID-19 mortality; however, many of these studies did not control for potential confounding factors, such as population size or demographics ( Katoto et al, 2021 ; Ali and Islam, 2020 ; Copat et al, 2020 ; Domingo et al, 2020 ). Among studies with some consideration of potentially confounding variables, several have reported positive associations between COVID-19 mortality and long-term air pollution concentrations, primarily PM 2.5 and NO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence, including this study, suggests long-term air pollution concentrations to be associated with COVID-19 mortality rates in an area (region, county, census tract, etc. ), indicating that communities with historically higher levels of ambient air pollution have a disproportionate burden of COVID-19 death ( Katoto et al, 2021 ; Ali and Islam, 2020 ; Wu et al, 2020 ; Lopez-Feldman et al, 2021 ; Liang et al, 2020 ; Konstantinoudis et al, 2021 ; Hutter et al, 2020 ). These communities likely face additional stressors, including exposure to higher levels of other risk factors for COVID-19 severity and mortality ( Singh et al, 2020 ; Ssentongo et al, 2020 ; Goodman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… **Studies assessing the effects of acute exposures presented substantial risks of bias. Katoto et al (2021) Role and potential association of air pollution especially particulate matter pollution in the transmission of COVID-19. **There appears to be a positive role of atmospheric particulate matter (PM) pollution and the spread of COVID-19.…”
Section: Recent Reviews On the Topicmentioning
confidence: 99%
“…But studies assessing the effects of acute exposures presented substantial risks of bias. 39 Some studies proposed that PM operates as a virus carrier, promoting its transport through the air. Exposure to ambient PM may also reduce the resistance to infection in the population although the degree of influence may depend on the particulate composition.…”
Section: Discussionmentioning
confidence: 99%